Visualisasi Pertumbuhan Janin Dalam Rahim Manusia sebagai Alternatif Media Pembelajaran - Tutik Susiani, Sri Siswanti (STMIK Sinar Nusantara, 2012)
Background The underlying problem is a lack of understanding of visualisas fetal growth is due to the education system with a book that makes the students feel bored. The purpose of the research is to create an application program to provide an alternative means of learning or extracting information and knowledge about the growth of the fetus. The method adalahn interviews, and literature. A literature study by studying the written material in the form of books related to the problem under study.The results of this research is the application of the growth of the human fetus in the womb as an alternative in the form of visual learning, making it easier for teachers and students in studying the growth of the human fetus in the womb.Key Words: visualization, fetal growth, instructional media, human uterus